Optical flow based violence detection from video footage using hybrid MobileNet and Bi-LSTM - Haque, Tashfia; Ahmed, Farhan Fuad; Ahmed, S. M. Irfan; Siam, Mohammad (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.